Comparative historical analysis of the foundation of classical gymnasium in the first quarter of the 19th century: Russian and international experience - A. N. Dzhurinskiy; N. V. Troshkova (Obrazovanie i Nauka, 2020)
Introduction. Improving the theory and practice of modern school dictates the need to take into account the historical and pedagogical heritage. There is a request for an in-depth and unbiased review of the history of Russian education and training. The search for effective pedagogical solutions actualises the appeal to the historical experience of Russian pedagogy, to the ideas and practices of classical education, which undeservedly remain outside the field of vision of Russian scholars and reformers of the modern Russian school.Aim and main research questions. The aim of the present research is to study the genesis of the Russian classical gymnasium in the first quarter of the 19th century. The study is an attempt at a dialogue with the past of Russian education, prompted by the intention to look into its future.This research work involves the analysis of the issues related to social and pedagogical factors, events in the process of the foundation and development of the Russian gymnasium as a new type of educational institution, and the comparison of its genesis with similar educational institutions in the West, taking into account the current problems of Russian school and education.The hypothesis of the research consists in scientific argumentation of the assessments of the foundation of the Russian classical gymnasium in the first quarter of the 19th century as a qualitatively new and important phenomenon of Russian education, which significantly influenced the further development of the Russian school.Methodology and research methods. The object of the study is the education system in Russia in the first quarter of the 19th century, and its subject is the classical gymnasium education of the indicated period. The foundation of a classical gymnasium is studied on the basis of the methodology of history of pedagogy and comparative pedagogy. The main methodological principles of historical and pedagogical science were taken into account – objectivity, historicism, comprehensiveness and consistency. In accordance with the methodology of objective positivism, the authors have made an attempt to scientifically understand and generalise the research findings and phenomena. The formulation of scientific ideas and judgments also required an appeal to the philosophy of relativism. The implementation of the methodology of comparative pedagogy provided for the search for similarities and differences, common and specific in the experience of the Russian classical gymnasium and secondary educational institutions of classical education in the West in the first quarter of the 19th century.When choosing research methods, the authors conducted the analysis of the presentation range of documents. The authors analysed more than 20 previously unpublished and unknown sources of archival holdings of the Russian State Historical Archive (St. Petersburg). Also, the authors analysed the Russian and foreign research papers published from the 19th century to the early 21st century.Research results. The genesis of the classical Russian gymnasium in the first quarter of the 19th century is presented for the first time in a holistic form: the establishment of a gymnasium under the Charter of 1804, the contribution of S. S. Uvarov to the creation of a classical gymnasium and his experiment in the St. Petersburg provincial gymnasium of 1811, the curriculum of gymnasiums of 1819, the official policy as a factor in the development of classical education. The authors compared the genesis of the Russian classical gymnasium and institutions of classical secondary education in the West in the first quarter of the 19th century.The research results demonstrate that the researched period was the key for the foundation of the classical Russian pre-revolutionary gymnasium. In Russia, a new sector of the education system was created, being in tune with the European pedagogical trends of the era. A shift of the Russian gymnasium by the end of the first quarter of the 19th century away from the encyclopedic curriculum of the beginning of the century to the strengthening of classicism was identified. The similarities and differences of the processes of its foundation compared to the genesis of complete general education in the West, especially in Prussia, are shown.Practical and scientific significance. The possibilities of updating the experience of Russian classical education in modern conditions are outlined. Turning to such experience allows us to more successfully solve not only the specific problems of the revived gymnasiums and gymnasium classes in modern Russia, but also, in general, to comprehend the prospects of classical education in the post-industrial era.